Loss of human leucocyte antigen class I and gain of class II expression are early events in carcinogenesis: clues from a study of Barrett's oesophagus. Issue 9 (7th February 2006) - Rajendra, S; Ackroyd, R; Karim, N; Mohan, C; Ho, J J; Kutty, M K
Abstract : Background: Human leucocyte antigen (HLA) expression is altered in oesophageal carcinomas compared with normal tissue. It is unclear, however, whether this phenotype precedes malignant transformation or results as a consequence of it. Aim: To investigate HLA class I and II expression in Barrett's oesophagus and normal squamous oesophageal tissue. Methods: Asian patients with Barrett's oesophagus (n = 64) and a control group (n = 60) with a normal oesophagus but without reflux symptoms were recruited using endoscopic and histopathological criteria. Tissue samples were stained with monoclonal antibodies specific for HLA-ABC, HLA-DR α chain or HLA-DP/DQ/DR, and scored semiquantitatively. The results of immunohistochemical staining were correlated with clinical and histopathological characteristics of patients. Results: Marked expression of HLA-ABC was observed in 50% of Barrett's oesophagus sections as compared with 68.3% of controls (p = 0.038). HLA-DR staining was seen in 51.6% of Barrett's oesophagus samples versus 11.7% of controls (p<0.001). Expression of HLA-DP/DQ/DR was evident in 73.4% of oesophageal intestinal metaplasia tissue as opposed to 18.3% of controls (p<0.001). Importantly, a total loss of HLA-ABC and a concomitant gain of HLA-DP/DQ/DR expression were seen in 37.5% of patients with Barrett's oesophagus but in none of the controls (p<0.001). Interestingly, this phenotype was associated positively with dysplasia (adjusted p, p* = 0.031) but negatively with non-steroidal anti-inflammatory drug use (p* = 0.004). Conclusions: HLA class I expression is down regulated and class II expression is up regulated in Barrett's oesophagus. As these changes predate malignant transformation, altered major histocompatibility complex expression may be a key event in disease progression, possibly in facilitating evasion from immune surveillance.